2002
DOI: 10.1114/1.1481053
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Fractal Dynamics of Human Respiration: Age and Gender Effects

Abstract: Abstract-We sought to quantify the fractal scaling properties of human respiratory dynamics and determine whether they are altered with healthy aging and gender. Continuous respiratory datasets ͑obtained by inductive plethysmography͒ were collected from 40 healthy adults ͑10 young men, 10 young women, 10 elderly men, and 10 elderly women͒ during 120 min of spontaneous breathing. The interbreath interval ͑IBI͒ time series were extracted by a new algorithm and fractal scaling exponents that quantify power-law co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
191
2
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 258 publications
(202 citation statements)
references
References 36 publications
5
191
2
4
Order By: Relevance
“…The use of approximate entropy also allowed Akay et al (2003) to describe age-related changes in the complexity of respiratory pattern, and to demonstrate that an hypoxic insult to the brain resulted in a decreased respiratory complexity (Akay and Sekine, 2004). Fractal fluctuations have been described in spontaneously breathing healthy adult humans (Fadel et al, 2004) and a decrease in respiratory complexity with age has also been shown by Peng et al (2002) through the analysis of fractal scaling exponents. Baldwin et al (2004), exploring the role of sigh in respiratory control with a combination of linear and nonlinear approaches (including long-range memory studied from detrended fluctuation analysis) showed that sighs were followed by a "restoration" of respiratory complexity under the form of an increase in the range of points located within a defined attractor.…”
Section: Discussionmentioning
confidence: 99%
“…The use of approximate entropy also allowed Akay et al (2003) to describe age-related changes in the complexity of respiratory pattern, and to demonstrate that an hypoxic insult to the brain resulted in a decreased respiratory complexity (Akay and Sekine, 2004). Fractal fluctuations have been described in spontaneously breathing healthy adult humans (Fadel et al, 2004) and a decrease in respiratory complexity with age has also been shown by Peng et al (2002) through the analysis of fractal scaling exponents. Baldwin et al (2004), exploring the role of sigh in respiratory control with a combination of linear and nonlinear approaches (including long-range memory studied from detrended fluctuation analysis) showed that sighs were followed by a "restoration" of respiratory complexity under the form of an increase in the range of points located within a defined attractor.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, one might suggest that there are short-range correlations in the stride interval such that the current value is influenced by only the most recent stride intervals, but over the long term, the fluctuations are random. A third, less intuitive possibility is that the fluctuations in the stride interval exhibit long-range, fractal-like correlations, as seen in a class of scalefree phenomena including heart rate beat-to-beat fluctuations (Goldberger et al, 2002;Peng et al, 1993;Peng et al, 1998;Peng et al, 1994;Peng et al, 2002). In this case, the stride interval at any instant would 'depend' (in a statistical mechanics sense) on the interval at relatively remote times, and this dependence would decay in a scale-free (fractal-like), powerlaw fashion.…”
Section: First Evidence Of Fractal-like Fluctuations In Gaitmentioning
confidence: 99%
“…Peng et al (24) used detrended fluctuation analysis to demonstrate the fractal nature of interbreath interval fluctuations in healthy adult subjects. We have confirmed this finding using a different method of fractal analysis, and, in addition, demonstrated fractal fluctuations of two other respiratory parameters.…”
Section: Discussionmentioning
confidence: 99%
“…The results indicate that, in most cases, apparently random fluctuations in respiratory pattern are, in fact, correlated over more than one time scale. Moreover, the data suggest that fractal fluctuations in breath number, respiratory period, and breath amplitude are controlled by separate processes.Allan and Fano factors; breath amplitude and frequency; dispersional analysis; Hurst exponent RESPIRATION IN AWAKE, HEALTHY adult humans is characterized by considerable variability in the frequency, duration, and amplitude of breaths (5,8,18,24,31). The aim of the present study was to define the basis for the variability of these respiratory parameters.…”
mentioning
confidence: 99%
See 1 more Smart Citation